Description of two new species of the genus Potamanthellus Lestage, 1931 (Ephemeroptera: Neoephemeridae) from India - Malaisamy Vasanth; Thangavel Kubendran; Kumarapuram Subramanian (نامه انجمن حشره‌شناسی ایران)
Two new species of the genus Potamanthellus Lestage viz., P. diversprimus sp. nov. and P. sineiugis sp. nov., were collected from the Eastern and Western Himalayan regions of India. This represents the first record of the family from these biogeographic regions. The two new species are described herein based on the larval stage from our recent exploration of mayflies in the streams and rivers of the Eastern and Western Himalayas of India.